Assessing the performance of analytical methods for propolis – A collaborative trial by the international honey commission. Issue 3 (27th May 2023) - Vilas-Boas, M.; Lopes, M.; Nunes, L. F.; Pereyra, A.; Kunert, C.; Beckh, G.; Çelemli, O. G.; Sorkun, K.; Georgé, S.; Paulo, L.; Gardini, S.; Sancho, M.T.; et al.
Abstract: Propolis is a resinous beehive product with extraordinary bioactivity and chemical richness, linked with the botanical sources of the resin. The potential of this product keeps captivating the scientific community, conducting to continuous and growing research on plant sources, composition, or applications in agriculture, cosmetics, pharmacy, odontology, etc. In all cases, the quality assessment is a requirement and relies on methods to extract the bioactive substances from the raw propolis and quantify different components. Unfortunately, besides the absence of international quality requirements, there is also a lack of standardized analytical procedures, despite the presence of several methodologies with unknown reliability, often not comparable. To overcome the current status, the International Honey Commission established an inter-laboratory study, with propolis samples from around the globe, to harmonize analytical methods and evaluate their accuracy. A common set of protocols was matched between twelve laboratories from nine countries, for quantification of ash, wax, and balsamic content in raw propolis, and spectrophotometric evaluation of total phenolics, flavone/flavonol, and flavanone/dihydroflavonol in the extract. A total of 3428 results (97% valid data), were used to assess the methods' accuracy following ISO-5725 guidelines. The within-laboratory precision, revealed good agreement levels for the majority of the methods, with relative variance below 5%. As expected, the between-laboratory variance increased, but, with exception of the flavanone method that revealed a clear lack of consistency, all the others maintained acceptable variability levels, below 30%. Because the performance of ultrasounds procedures was low, they cannot be recommended until further improvements are made.